An overview of monitoring tools for real-time cyber-attacks - Baykara, Muhammet; Gurturk, Ugur; Das, Resul (Ieee, 2018)
Network security refers to precautions and activities designed to protect the availability and integrity of data exchanged between the network and the digital world. Information security protects digital data from unauthorized access, disclosure, manipulation, alteration or destruction using both hardware and software technologies. According to an analysis by experts working in the field of information security, more than twenty thousand cyber-attacks per month are being made to a medium-sized company. As a result of the analyzes carried out, it has been determined that although the level of risk is not high in most of the attacks, it is an intense danger for important data and the severity of these attacks is increased. Systems that provide real-time analysis have been created to raise awareness of these increasing threats and cyber-attacks and to detect new attacks. In this study, we introduce an overview of software systems for real-time visibility into global cyber-attacks threat systems, which provide animations in real-time mappings based on information about cyber-attacks on the world, according to the destination/source country of the attack and species/detail information. Real-time monitoring tools are designed to monitor for specific traffic patterns that are indicative of malicious activity.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: network security; information security; network visualization; honeypot systems